2022
DOI: 10.3390/ma15093192
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of One-Dimensional Polyaniline Nanotubes as Anticorrosion Coatings

Abstract: Uniform polyaniline (PANI) nanotubes were synthesized by a self-assembly method under relatively dilute hydrochloric acid (HCl) solution. Scanning electron microscopy (SEM), Fourier transform infrared (FTIR) spectroscopy, and UV-Vis-NIR spectroscopy were employed to characterize the morphology and molecular structure of the PANI products. SEM images show that the PANI nanotubes have uniform morphology and form compact coating on the substrate surface. For comparison, aggregated PANI was also synthesized by con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…The peak at 1496 cm −1 is attributed to C=C stretching of benzenoid rings 18 . In addition, the appearance peaks at 1300 and 1238 cm −1 are assigned to the C‐N stretching of quinoid rings, while the peaks at 1138 and 801 cm −1 are corresponded to the aromatic C‐H in‐plane bending and the out‐of‐plane deformation of C‐H 27,34,35 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The peak at 1496 cm −1 is attributed to C=C stretching of benzenoid rings 18 . In addition, the appearance peaks at 1300 and 1238 cm −1 are assigned to the C‐N stretching of quinoid rings, while the peaks at 1138 and 801 cm −1 are corresponded to the aromatic C‐H in‐plane bending and the out‐of‐plane deformation of C‐H 27,34,35 …”
Section: Resultsmentioning
confidence: 99%
“…33 The peak at 1496 cm À1 is attributed to C=C stretching of benzenoid rings. 18 In addition, the appearance peaks at 1300 and 1238 cm À1 are assigned to the C-N stretching of quinoid rings, while the peaks at 1138 and 801 cm À1 are corresponded to the aromatic C-H in-plane bending and the out-of-plane deformation of C-H. 27,34,35 Figure 2e,f show the TG and DTG curves of JNSs and PANI@JNSs. JNSs contain three weight loss stages at about 25-116 C, 116-265 C and 265-575 C, which are respectively corresponded to the removal of free water, the elimination of bonding water and the decomposition of organic groups as amino group, carbonyl groups, double bonds and saturated alkyl groups.…”
Section: Morphology and Chemical Composition Of Jnss And Pani@jnssmentioning
confidence: 99%
“…Replacing toxic or expensive inhibitors with some organic compounds represents the desired goal of many scientists. PANI, as a target material in this paper, (Tian et al, 2014;G. Yang et al, 2022), is among the most extensively researched ECPs in corrosion inhibition of ferrous and non-ferrous materials.…”
Section: Pani-based Inhibitorsmentioning
confidence: 99%
“…Another recent work by Yang et al . reported that tube‐like PANI was successfully formed in dilute acid media; the formed PANI showed excellent anticorrosion properties owing to the formation of a compact coating on the substrate surface 25 . Apparently, the synthesis conditions of COP are worth investigating as PANI with different morphological and electrical properties is needed for different applications.…”
Section: Introductionmentioning
confidence: 99%